PENGEMBANGAN BAHAN AJAR SCIENCE ENTREPRENEURSHIP BERBASIS HASIL PENELITIAN UNTUK MENDUKUNG PROGRAM KREATIVITAS MAHASISWA - Martin HB., F. Putut (Jurnal Penelitian Pendidikan, 2012)
This study is the kind of research that aims to generate development of instructional materials science entrepreneurship in order to improve students’ ability in developing a proposal Student Creativity Program (PKM). Teaching materials science-based entrepreneurship research results developed and used in learning, teaching materials were evaluated and validated before being used first, then followed up with a proposal for a student paper competition. The results obtained in this study include the development of teaching materials - used in student learning as a stimulus produces PKM proposals and the effectiveness of instructional materials such as determined from the results of student learning in the form of the value end of the semester. Based on these results, it can be concluded that entrepreneurship teaching materials developed science-based research to obtain an expert assessment of viable entrepreneurial experts, students are able to draw up a proposal Student Creativity Program (PKM) well after the use of teaching materials developed in the subject of science and entrepreneurship the use of instructional materials science entrepreneurship effectively developed based on student learning.